Obstructive uropathy and acute renal failure due to ureteral calculus in renal graft: a case report - Lusenti, T. (Elsevier, 2009)
INTRODUCTION: Obstructive uropathy caused by kidney stones is quite rare in transplant kidneys. CLINICAL CASE: The authors report the case of a patient, previously gastrectomized for gastric carcinoma. He underwent renal transplantation using uretero-ureterostomy, and presented an episode of acute renal failure 7 years after surgery. Ultrasound (US) examination showed no sign of rejection but allowed detection of moderate hydronephrosis in the transplant kidney. Subsequent computed tomography (CT) revealed a kidney stone in the middle ureter at the crossing of the iliac vessels. The patient therefore urgently underwent percutaneous nephrostomy of the graft and recovered diuresis and renal function. The patient was transferred to the Transplant Center where he underwent ureterotomy with removal of the stone and subsequent ureteropyelostomy. Also transureteral resection of the prostate (TURP) was performed due to urinary retention of prostatic origin. Histological examination showed prostate carcinoma, Gleason stage 3, which was treated conservatively using radiotherapy without suspension of the administered low dose of immunotherapy. DISCUSSION: Calculosis is one of the least common causes of obstructive uropathy in transplant kidneys. In the described case, US examination performed after onset of renal insufficiency led to subsequent radiological investigation and resulting interventional procedures (nephrostomy and surgical removal of the stone) with complete recovery of pre-existing renal function.